2019
DOI: 10.11111/jkana.2019.25.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of ICU Nurses' Difficulties in End-of-Life Care to Moral Distress, Burnout and Job Satisfaction

Abstract: Purpose:The aim of this study was to identify the relationships between the difficulty of end-of-life care and moral distress, burnout and job satisfaction of nurses working in intensive care units (ICUs). Methods: This descriptive study was conducted using self-report questionnaires. Participants were nurses who had more than one year of ICU experience and were recruited from three university hospitals (N=168). Results: The mean scores for ICU nurses' difficulty in end-of-life care, moral distress, burnout an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Early studies on this topic were confined to the intensive care setting [ 4 , 5 ], specifically related to end-of-life treatment [ 6 , 7 ]. However, empirical research on this topic has seen exponential growth in recent years, intensifying the study of moral distress in any other clinical care setting (long-term care facilities, pediatric or neonatal settings and emergency or mental health departments) [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies on this topic were confined to the intensive care setting [ 4 , 5 ], specifically related to end-of-life treatment [ 6 , 7 ]. However, empirical research on this topic has seen exponential growth in recent years, intensifying the study of moral distress in any other clinical care setting (long-term care facilities, pediatric or neonatal settings and emergency or mental health departments) [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Dodek et al suggested that higher moral distress in ICU nurses was associated with higher psychological stressors and psychological strain (39). Jeon and Park suggested that nurses working in ICU wards suffered from moral distress due to difficulties at the end of life care and realist support in the workplace (40). Recent studies also indicate high levels of moral distress in nurses responsible for caring for COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…과 Park [16]이 간호사의 소진 관련 요인을 조사한 선행연구에 근거 하여 G*power 3.1.9.4 프로그램을 이용하여 검정력 .80, 유의수준 .05, 중간효과크기 .15로 설정하였고, 일반적 특성 13개, 의사소통 능력, 간호전문직관, 스트레스 대처 하위 영역 2개를 포함하여 총 17 개의 예측요인을 투입하여 단계적 다중 회귀분석(stepwise multiple regression analysis)을 근거로 산출한 결과 146명으로 산출되 었다. 탈락률 10%를 고려하여 163명을 대상으로 설문지를 배부하여 160부를 회수하였고, 응답이 불충분한 설문지 11부를 제외한 총 149부를 자료 분석에 포함하였다.…”
Section: 연구대상unclassified